Avaliação da segurança da operação de sistemas elétricos de potência considerando os limites de estabilidade angular e de tensão - Mariotto, Lenois (2008)
This work presents new analytical and computational methods for operation security assessment of electric power systems by considering Angle and Voltage Stability Limits. In the context of Angle Stability, it was developed a method for estimating transient security margins based on equivalent network reduction techniques and coherent generators. The angle speed deviation was the criterion used to identify generators that swing together. The reduced order was accomplished by replacing two clusters of coherent generators by an One-Machine Infinite Bus equivalent system. With this equivalent, critical fault clearing times and security margins are calculated with the aid of the Equal Area Criterion. The results were in a good agreement when compared with others methods, especially those based on Transient Energy Function used as a Lyapunov function. The method was also applied for estimating security margins and critical fault clearing times of power systems in the presence of wind power generation. It was demonstrated that the proposed method can be used to select critical contingencies, where detailed power system models are needed such that it can reproduce the actual behavior of the system. With respect to Voltage Stability, it was developed an analytical and computational method for steady state voltage stability analysis on a P-Q plane. First of all, it was applied on a simple two-bus power system, and the analytical and computational results were compared. Then, a Voltage Stability Index was derived, in order to obtain the security margins of each bus for any operational state of an n-bus power system. It was carried out by using a power system reduction technique. With the Voltage Stability Index, it is possible to identify critical buses and the regions that are prone to voltage collapse. The voltage stability limits of a distribution power system was also analyzed by means of the P-Q curves, by considering different operation scenarios of wind power generation. It was demonstrated that the wind power can contribute to improve the voltage security margins. Finally, the method was applied to a real power system of Companhia Estadual de Distribuição de Energia Elétrica, in the presence of wind power generation. The methods are computationally efficient and suitable for planning, operation and real-time operation of electric power systems.